Harnessing heterosis in eggplant (Solanum melongena L.) - Harshita Thota* and I. R. Delvadiya (Electronic Journal of Plant Breeding)
A study was undertaken to examine the extent of heterosis and to identify promising parents and superior crosses in eggplant for yield and its component traits. The experiment consisted of 36 hybrids generated by half diallel mating, nine parents and a standard check. The trial was laid out in a randomized block design with three replications at the research farm, School of Agriculture, LPU, Punjab, during the kharif season of 2022-2023. Analysis of mean squares for 10 traits revealed significant variations among the entries. Heterotic effects, including heterobeltiosis and standard heterosis, exhibited a broad range indicating extensive heterosis for various traits. The hybrid JBR-3 x JBR-5 proved to be the top performer, displaying the highest heterobeltiosis and standard heterosis for total fruit yield per plant, followed by JBL-1 x JBR-5, JBR-4 x JBR-5, JBR-1 x JBR-5, and JBR-5 x JBR-6. The combination JBR-3 x JBR-5 showcased the highest positive and significant standard heterosis for total yield per plant (154.49%) and also exhibited notable negative heterosis for days to 50% flowering (-20.37%), days to first picking (-8.61%), and fruit borer infestation (-40.08%). These factors are vital for leveraging heterosis to improve earliness and resistance in brinjal cultivation. The F1 hybrid JBR-3 x JBR-5, demonstrating a notable capacity for high yield, holds promise for potential commercial cultivation after further assessment.